Efforts to Discipline Santri in Foreign Languages After The Enactment of the Child Protection Law Number 23 of 2002 - Samhudi, Samhudi; Sani, Ahmad (Sekolah Tinggi Agam Islam Sumatera Medan, 2024)
Santri in Dayah are required to use foreign languages in the school environment. Those who violate this rule will receive sanctions. Previously, corporal punishment was often given to students who did not comply, but this is clearly contrary to Law Number 23 of 2002 concerning Child Protection. In this regard, this study aims to analyze the problems faced by Dayah Ulumuddin Lhokseumawe in enforcing the language discipline of students after the enactment of the Law, as well as the efforts made in disciplining foreign language students. This research method uses a descriptive analysis-based qualitative method, in which case observation interviews, and documentation studies become data collection techniques. The results of the study reveal that the problems faced by teachers in disciplining foreign-speaking students are the teacher's concern that the disciplinary actions taken by students will be legally problematic, which results in a decrease in the enthusiasm of teachers to enforce the discipline of foreign-speaking students. The disciplinary efforts made are revising the punishment for language violations into educational punishments, innovating language coaching programs, balancing rewards and punishments, increasing learning motivation, and socializing child protection laws to those responsible for enforcing foreign language discipline. This research has implications for the effectiveness of foreign language discipline enforcement among dayah students.